Increased Serum Soluble Transferrin Receptor Levels Were Associated With High Prevalence of Cardiovascular Diseases: Insights From the National Health and Nutrition Examination Survey 2017–2018 - Zhu, Shiyu; Liu, Chang; Zhao, Chengchen; Chen, Guanzhong; Meng, Simin; Hong, Ma; Xiang, Meixiang; Xie, Yao (Frontiers in Cell and Developmental Biology, 2022)
Background: Iron deficiency is common in cardiovascular diseases (CVD), e.g., heart failure and coronary heart disease. Soluble transferrin receptor (sTfR) is a promising marker representing unmet cellular iron demands. However, whether higher serum sTfR is associated with increased risk of CVDs needs further investigation. Methods: In the present cross-sectional study, we analyzed data of 4,867 adult participants of the National Health and Nutrition Examination Survey (NHANES) 2017–2018. Linear regression models were employed to identify possible correlations between sTfR and other characteristics. The association between sTfR and CVDs was assessed with univariable and multivariable logistics regression models. Results: The prevalence of CVDs was 9.5% among participants, and higher sTfR levels were found in participants with CVDs (p < 0.001). Linear regression models revealed positive associations between sTfR and age, body mass index, systolic blood pressure, glycated hemoglobulin A1c, and insulin resistance (all p < 0.001). In the multivariable logistics regression model, the adjusted odds ratio of sTfR for CVDs was 2.05 (per 1 log2 mg/L, 95% confidence interval: 1.03∼4.05, p = 0.046). Further subgroup analysis identified the associations of sTfR and CVDs were only significant in participants ≥60 years old, or with hypertension (all p < 0.05). Conclusion: Our study demonstrated that increased serum sTfR levels were associated with a high prevalence of cardiovascular diseases.